The financial crisis: : what lessons can be learned? - Kowalski, Tadeusz; Shachmurove, Yochanan (Economics and Business Review, 2011)
Many are currently studying the origins of the financial crisis in an attempt to answer two seemingly simple questions: why did it happen, and can another crisis be prevented? Those two questions have proved incredibly divisive. The majority opinion of The United States Financial Crisis Inquiry Commission was submitted with two dissenting positions. Furthermore, The 2010 Economic Report of the United States President does not perfectly align with any opinion presented in that report. Few studies, however, provide proper consideration to the evolution of macroeconomic thought and lengthening of the business cycle preceding the current crisis. (original abstract)